2012
DOI: 10.4149/gpb_2012_032
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the mesenteric bed arteries of normotensive rats exposed to chronic social stress

Abstract: The aim of this study was to investigate the effects of chronic social stress on endothelium-dependent relaxation in the superior mesenteric artery (SMA) and its first branches (1MA) as well as on neurogenic contractions of SMA in adult, male Wistar-Kyoto (WKY) rats. Mesenteric arteries were isolated from control (living space: 480 cm(2)/rat) or stressed rats exposed to 8-week-lasting crowding stress (living space: 200 cm(2)/rat). Blood pressure (BP) and heart rate, determined by tail-cuff plethysmography, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In an animal study conducted by Isingrini et al (153), unpredictable chronic mild stress induced hormonal and depression-related physical behaviors along with decreased endothelium-dependent vasorelaxation. In this study, stress did not affect phenylephrine-induced vasoconstriction, whereas Puzserova et al (268) reported increased contractile responses to both electrical stimulation of perivascular nerves and exogenous norepinephrine without any discernible changes in nitric oxide (NO)-dependent vasorelaxation. Results from another experiment suggest that chronic mild stress increased phenylephrine-induced vasoconstriction in intact aortic ring segments, yet failed to show such effects in N G -nitro-L-arginine methyl ester-incubated or endothelium-denuded rings.…”
Section: A Central Role For the Endotheliummentioning
confidence: 51%
“…In an animal study conducted by Isingrini et al (153), unpredictable chronic mild stress induced hormonal and depression-related physical behaviors along with decreased endothelium-dependent vasorelaxation. In this study, stress did not affect phenylephrine-induced vasoconstriction, whereas Puzserova et al (268) reported increased contractile responses to both electrical stimulation of perivascular nerves and exogenous norepinephrine without any discernible changes in nitric oxide (NO)-dependent vasorelaxation. Results from another experiment suggest that chronic mild stress increased phenylephrine-induced vasoconstriction in intact aortic ring segments, yet failed to show such effects in N G -nitro-L-arginine methyl ester-incubated or endothelium-denuded rings.…”
Section: A Central Role For the Endotheliummentioning
confidence: 51%
“…Recent human and animal studies have further demonstrated that stress can also lead to the development of vascular dysfunction resulting in a predisposition to CVD [ 154 157 ]. In addition, both acute and chronic stressors have been shown to impair vascular reactivity.…”
Section: Comorbidity Of Stress-related Mood Disorders and Systemicmentioning
confidence: 99%
“…In addition, both acute and chronic stressors have been shown to impair vascular reactivity. Although the exact mechanism and effect seem to be dependent on the type of the stressor and/or the model, there is evidence to suggest that reduced vascular dilation and enhanced constriction may play an important role [ 156 , 157 ]. In humans, acute psychological stress reduces the magnitude of flow-mediated dilation of the brachial artery, a measure of the reactivity of the peripheral vasculature that is thought to be the result of altered nitric oxide handling [ 154 ].…”
Section: Comorbidity Of Stress-related Mood Disorders and Systemicmentioning
confidence: 99%
“…Experimental cardiovascular pathologies are associated with different neuropsychiatric symptoms, while on the contrary, various mental disorders may support the progression of cardiovascular, neurohumoral or metabolic disorders (Pechanova et al 2006;Bernatova et al 2010;Puzserova et al 2012;Aziriova et al 2016;Olexova et al 2016;Pokusa et al 2016;Senko et al 2017;Repova et al 2018). In a clinical setting, patients with cardiac diseases suffer from post-traumatic stress disorder (Vilchinsky et al 2017), yet mental disorders not only impair their adherence to therapeutic management (Gentil et al 2017); they can also contribute to the progres-sion of cardiovascular diseases (Shields and Slavich 2017).…”
mentioning
confidence: 99%